2013
DOI: 10.1186/1472-6882-13-188
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel openers and prostacyclin play a crucial role in mediating the vasorelaxant activity of Gynura procumbens

Abstract: BackgroundPrevious studies of Gynura procumbens (G. procumbens) have shown that partially purified fractions of the leaves are capable of lowering the blood pressure of rats by inhibiting angiotensin-converting enzymic activity and causing vasodilatation. The objectives of this study were therefore to further purify the active compounds that exhibited selective effects on blood vessels, determine the mechanism of actions, and to qualitatively analyse the putative compounds present.MethodsThe butanolic fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
3
22
2
Order By: Relevance
“…The affirmation of the relaxing effect of PFRE in coronary artery may implicate important implementation of the plant in patients with myocardial and coronary artery disease, that's why P. farcta has long been used as a traditional remedy for angina pectoris [22], reducing cardiac or chest pain and for managing cardiovascular disorder in Iran [19], as a therapeutic agent in treating cardiovascular disorders [23] [39] . However, the result somewhat conflicts the earlier finding of [22] Vascular contractions implicate the control of K + channels, the opening of K + channels in VSMCs results from the outward current of K + and membrane hyperpolarization which in turn results in a reduction in Ca +2 entry as a result from the closure of VDCC, and vasodilation [40].…”
Section: Discussioncontrasting
confidence: 89%
“…The affirmation of the relaxing effect of PFRE in coronary artery may implicate important implementation of the plant in patients with myocardial and coronary artery disease, that's why P. farcta has long been used as a traditional remedy for angina pectoris [22], reducing cardiac or chest pain and for managing cardiovascular disorder in Iran [19], as a therapeutic agent in treating cardiovascular disorders [23] [39] . However, the result somewhat conflicts the earlier finding of [22] Vascular contractions implicate the control of K + channels, the opening of K + channels in VSMCs results from the outward current of K + and membrane hyperpolarization which in turn results in a reduction in Ca +2 entry as a result from the closure of VDCC, and vasodilation [40].…”
Section: Discussioncontrasting
confidence: 89%
“…Vasocontraction caused by phenylephrine, calcium and potassium chloride was shown to be antagonized by G. procumbens extracts. This was probably due to the blocking of receptor-operated and/or voltage dependent calcium channels as well as opening of potassium channel (Hoe et al, 2011; Ng et al, 2013). Therefore, G. procumbens potentially serves as an antihypertensive agent with cardioprotective activity due to its ability to target various mechanisms including the renin-angiotensin system and calcium influx which are crucial players in the pathophysiology of hypertensive conditions.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…This evergreen shrub grows extensively in Southeast Asia and is locally known in Malaysia as Sambung Nyawa . Several studies have reported that this herb possesses anti-inflammatory [9], antihypertensive [10], anti-cancer [11], and antihyperglycaemic [12, 13] activities and recently has been recognised as a profertility factor [14]. The administration of GP aqueous extract (GPAE) was reported to reduce blood glucose levels significantly and increased sperm quality [14].…”
Section: Introductionmentioning
confidence: 99%